Problems and prospects of implementation controlling as a modern enterprise management tool - Mykhaylychenko, N.; Tokareva, A. (Економічний вісник Донбасу, 2016)
The article includes problematic aspects implementation of the introduction of controlling in the enterprise. Identified the basic approaches and principles of organizations and implementation controlling. Described the basic problem faced by enterprises in the during organization and implementation controlling. Considered problems arising in case of implementing controlling service in the enterprise, and ways of solutions. Also developed the scheme implementing a mechanism for controlling in management system and provided characteristics of the stages of implementation of this scheme. Today controlling system is not implemented in administrative practice of Ukraine, so you should prioritize the direction of domestic enterprises, the possibility of their competition with foreign enterprises in the future and prospects of economic development, which allows the introduction of controlling.